2005
DOI: 10.1001/archpsyc.62.1.85
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Serotonin Transporter Promoter Gene and Shyness on Children’s Cerebral Responses to Facial Expressions

Abstract: Children who manifest higher levels of shyness or have 1 or 2 copies of the short allele of the serotonin transporter promoter gene appear to have a different pattern of processing affective stimuli of interpersonal hostility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
114
0
4

Year Published

2007
2007
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 176 publications
(125 citation statements)
references
References 53 publications
7
114
0
4
Order By: Relevance
“…This is consistent with the vigilance-avoidance hypothesis which states that negative emotional expressions are especially threatening to shy individuals, and that emotion-processing deficits reflect avoidance of emotion-specific stimuli following a brief period of increased attention to them (Mogg, Bradley, de Bono, & Painter, 1997). The emotion thought to most profoundly activate this information processing sequence is anger, although other negative emotions may also trigger the response (Battaglia et al, 2005;Stirling et al, 2006).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…This is consistent with the vigilance-avoidance hypothesis which states that negative emotional expressions are especially threatening to shy individuals, and that emotion-processing deficits reflect avoidance of emotion-specific stimuli following a brief period of increased attention to them (Mogg, Bradley, de Bono, & Painter, 1997). The emotion thought to most profoundly activate this information processing sequence is anger, although other negative emotions may also trigger the response (Battaglia et al, 2005;Stirling et al, 2006).…”
Section: Discussionsupporting
confidence: 87%
“…Drawing on a non-clinical sample, Battaglia and colleagues (Battaglia et al, 2004) reported that higher scores on a teacher-completed measure of social anxiety predicted poorer performance on a facial emotion identification task for second-and third-grade children. In a later study, that group found that, in response to stimuli depicting negative facial emotions, individuals with a genetic marker for shyness had a different pattern of event-related potentials than did those without the marker (Battaglia et al, 2005). This finding and others are consistent with theorizing within neuroscience that shyness and the processing of direct expressions of emotion}particularly negative emotions such as anger}-should be related because both are mediated, in large part, by the same brain structures and functions (Schwartz, Wright, Shin, Kagan, & Rauch, 2003;Wahlen, 1998).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…An excellent example in the psychiatry literature of the definition of an endophenotype using genetics, ERP, neuroimaging, and behavioral testing, is the work focusing on the serotonin transporter gene and its association to mood disorders and personality traits, most robustly studied in social anxiety and shyness in children (Battaglia et al 2005;Canli and Lesch 2007;Gunthert et al 2007;Hayden et al 2007;Serretti et al 2006). Two common alleles of the serotonin transporter promoter (5-HTTPR), short and long, have been differentially associated with: level of serotonin uptake and transport, amygdala activity in response to angry or fearful faces, and behavioral phenotypes such as anxiety, avoidant personalities and shyness.…”
Section: The Futurementioning
confidence: 99%
“…A significant expression-genotype interaction was found. Children who were shy were most likely to have more 1 or 2 copies of the short allele of the 5-HTTPR, and to have smaller N400 amplitudes to angry and neutral faces (Battaglia et al 2005). One could imagine taking this work a step further by using emotion ERP paradigms coupled with genetic testing early in infancy to define children at risk for anxiety disorder, and then targeting early behavioral interventions to prevent social phobias.…”
Section: The Futurementioning
confidence: 99%